Syphilis and Urogenital Diseases during Pregnancy and Developmental Defects of Enamel: A Brazilian Prenatal Cohort (BRISA) - Elisa Miranda Costa; Judith Rafaelle Oliveira Pinho; Maria da Conceição Pereira Saraiva; Cecília Cláudia Costa Ribeiro; Claudia Maria Coêlho Alves; Erika Barbara Abreu Fonseca Thomaz (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate the effect of syphilis and urogenital diseases (SUD) during pregnancy on developmental defects of enamel (DDE) using causal inference models. Material and Methods: This study is a prospective cohort – the Brazilian Ribeirão Preto and São Luís Cohort Study (BRISA) – including 865 mother-child dyads, evaluated in three moments: prenatal care (22nd and 25th weeks of gestational age); baby birth; and between 12.3-36 months of age. The outcome was assessed according to the modified DDE index. The exposition, SUD, comprised at least one of the following infections: bacterial vaginosis, urinary tract infection, and syphilis. The covariables included in the theoretical model were socioeconomic situation (SES), low birth weight, mother’s age, number of prenatal care visits (PCV), hypertension, diabetes, medication use during pregnancy, and child’s age. Based on the proposed directed acyclic graph (DAG), SES and the number of PCV were the minimal set of covariables for the adjusted model. The effects were estimated by causal inference using a marginal structural model (Average Treatment Effect - ATE coefficients). Results: SUD did not interfere in the incidence of DDE (ATE: -0.92; CI95%: -0.23-0.49; p=0.202). Conclusion: SUD during pregnancy does not have a causal effect on DDE on primary dentition. Another possibility is that other infections not included in the model may have confounded the association, biasing toward the null hypothesis.